2018
DOI: 10.1038/s41386-018-0294-3
|View full text |Cite
|
Sign up to set email alerts
|

Dynorphin-kappa opioid receptor activity in the central amygdala modulates binge-like alcohol drinking in mice

Abstract: Although previous research has demonstrated a role for kappa opioid receptor-mediated signaling in escalated alcohol consumption associated with dependence and stress exposure, involvement of the dynorphin/kappa opioid receptor (DYN/KOR) system in binge-like drinking has not been fully explored. Here we used pharmacological and chemogenetic approaches to examine the influence of DYN/KOR signaling on alcohol consumption in the drinking-in-the-dark (DID) model of binge-like drinking. Systemic administration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 59 publications
3
49
0
Order By: Relevance
“…Nts CeA neurons also have a partial overlap with Pdyn CeA neurons. Dynorphin neurons in the CeA contribute to binge-drinking, a form of ethanol consumption that confers a high risk of developing alcohol use disorder (Anderson et al, 2019). We recently showed that dynorphin and NTS bi-directionally modulate synaptic inputs from the CeA to the BNST (Normandeau et al, 2018).…”
Section: Cea Neurotensin Neurons In Ethanol Consumptionmentioning
confidence: 99%
“…Nts CeA neurons also have a partial overlap with Pdyn CeA neurons. Dynorphin neurons in the CeA contribute to binge-drinking, a form of ethanol consumption that confers a high risk of developing alcohol use disorder (Anderson et al, 2019). We recently showed that dynorphin and NTS bi-directionally modulate synaptic inputs from the CeA to the BNST (Normandeau et al, 2018).…”
Section: Cea Neurotensin Neurons In Ethanol Consumptionmentioning
confidence: 99%
“…For example, a reduction of alcohol consumption in mice was found by a suppression of activity in the NAc core with hM4Di-mediated inhibition [ 130 ]. Pharmacological antagonism of the k-opioid receptor and chemogenetic silencing of dynorphin signaling neurons was used to identify a role for dynorphin/k-opioid receptor signaling in the central amygdala in excessive alcohol consumption in a rodent model of binge drinking [ 131 ]. Specific neuronal ensembles critical for alcohol dependent drinking within the CEA were identified by the chemogenetic silencing of activated neurons using Daun02 [ 91 ].…”
Section: Recently Developed Approaches In Preclinical Neurosciencementioning
confidence: 99%
“…Manner Previous studies employing pharmacological approaches have shown that KOR antagonism in the CeA can decrease alcohol intake (Anderson et al, 2018;Kissler et al, 2014). However, it remains unclear whether this is mediated by KOR expression on CeA neurons or on presynaptic terminals from other brain regions.…”
Section: Knockout Of Kor In Cea Reduces Alcohol Consumption and Prefementioning
confidence: 99%
“…In animal models, systemic treatment with KOR antagonists has been shown to reduce ethanol self-administration (Walker & Koob, 2007), stress-enhanced drinking (Anderson, Lopez, & Becker, 2016), and ethanol dependence-induced increases in anxiety (Valdez & Harshberger, 2012). Additionally site-specific KOR antagonism in the CeA decreases ethanol self-administration in dependent animals (Kissler et al, 2014) and alcohol consumption in a model of binge-like drinking (Anderson et al, 2018). Anderson et al (2018) also found that chemogenetic inhibition of preprodynorphin (PDYN) neurons in the CeA reduced binge-like drinking, suggesting that the source of dynorphin release may be within the CeA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation